2018
DOI: 10.1038/s41598-018-26683-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a peptide for folate receptor alpha by phage display and its tumor targeting activity in ovary cancer xenograft

Abstract: The expression level of folate receptor alpha (FRα) is located highly rate in ovarian cancer though it is remained absent in normal tissues. This highly tumor restricted expression profile makes FRα a promising target for tumor therapy and diagnosis. In this research we report a FRα binding peptide C7(Met-His-Thr-Ala-Pro-Gly-Trp-Gly-Tyr-Arg-Leu-Ser) discovered by phage display and this peptide showed specific binding to FRα expressing cells by cell ELISA and flow cytometry. Tumor targeting ability of C7 was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Thus, these results clearly confirmed the correct design of the peptide-based controlled delivery system created for this multifunctional silica-based nanodrug. In fact, the anti-proliferative activity enhancement of organotin metallodrug MSNs was achieved only in the case of interaction with tumor cells from breast adenocarcinoma that have been described overexpressing both folate receptor alpha and the cathepsin B enzyme, being this last the responsible of peptide cleavage and the metallodrug release [59,66,67]. Besides the antiproliferative activity, we decided to evaluate also the potential inhibition of migration ability of MDA-MB-231 cells by means of wound healing assay (Figure 7).…”
Section: In Vitro Characterization Of the Different Msn-based Multifumentioning
confidence: 99%
“…Thus, these results clearly confirmed the correct design of the peptide-based controlled delivery system created for this multifunctional silica-based nanodrug. In fact, the anti-proliferative activity enhancement of organotin metallodrug MSNs was achieved only in the case of interaction with tumor cells from breast adenocarcinoma that have been described overexpressing both folate receptor alpha and the cathepsin B enzyme, being this last the responsible of peptide cleavage and the metallodrug release [59,66,67]. Besides the antiproliferative activity, we decided to evaluate also the potential inhibition of migration ability of MDA-MB-231 cells by means of wound healing assay (Figure 7).…”
Section: In Vitro Characterization Of the Different Msn-based Multifumentioning
confidence: 99%
“…The folate receptor is a cell surface glycoprotein receptor that is able to bind to folate with high affinity and mediate the unidirectional transport of folate into cells. Folate has been used for targeting cancers and tumors, as folate receptors are highly expressed on the surface of many types of tumors [ 42 ]. The high affinity of the folate receptor that is preferentially expressed in cancer cells is rarely expressed in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The high affinity of the folate receptor that is preferentially expressed in cancer cells is rarely expressed in normal cells. This has allowed the development of the targeted delivery of anticancer drugs at the cancer at the tumor sites to maximize anticancer efficacy with minimizing side effects to healthy tissues [ 42 , 43 , 44 , 45 ]. The folate targeting of cancerous cells has been reported recently in many studies; e.g., L. Xing et al 2018 used folate targeting for ovary cancer cells, and found that folate receptor alpha (FRα) is overexpressed in ovary cancer cells [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…We show that synthetic TVRTSAE peptide binds SKOV3 cells in a dose-dependent manner and binds via the FRα since binding was inhibited when cells were pretreated with the FRα ligand folic acid. In similar studies, peptide MHTAPGWGYRLS was identified as a FRαspecific peptide using the same Ph.D-12 phage-display library for biopanning SKOV3 cells [42]. Peptide SWQIGGN was found to target HO8910 ovarian cancer cells in vitro, inhibiting cell viability, migration invasion…”
Section: Discussionmentioning
confidence: 99%